1974
DOI: 10.1121/1.1903512
|View full text |Cite
|
Sign up to set email alerts
|

Time-frequency-domain formulation of ultrasonic frequency analysis

Abstract: The ultrasonic frequency spectrum is interpreted by Fourier analysis techniques. This approach leads to the same conclusions concerning flaw characterization as previous interference models; in addition, a number of other spectral characteristics are easily explained. Finally, the present treatment indicates that frequency analysis may be applicable to many additional problems, viz., timing measurements of any type (e.g., thickness or velocity measurements), wide-band attenuation measurements, and phase-shift … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
10
0
1
Order By: Relevance
“…Analysis of ultrasonic waves which have been transmitted through a sample allow acoustic and hence mechanical parameters of the sample to be extracted. In most cases, signals are not overlapped and both time domain [1] and frequency domain [2,3] analysis can be used to determine parameters such as wave velocity, attenuation or density.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of ultrasonic waves which have been transmitted through a sample allow acoustic and hence mechanical parameters of the sample to be extracted. In most cases, signals are not overlapped and both time domain [1] and frequency domain [2,3] analysis can be used to determine parameters such as wave velocity, attenuation or density.…”
Section: Introductionmentioning
confidence: 99%
“…The velocities of the separated shear‐wave modes are different. When two shear‐wave modes travel in the same direction, interference effects are produced . After the two shear‐wave modes with interference effects are reflected from the steel‐member rear side, they return to the shear‐wave transceiver probe.…”
Section: Theorymentioning
confidence: 70%
“…The synthesis signal of the two shear‐wave modes contains stress information, which is the basis of this method, to measure stress by evaluating the change of the shear‐wave spectrum. Simpson investigated the birefringence‐induced interference effect of two shear waves and established the fundamental procedures for measuring stress using the shear‐wave spectrum. Blinka and Sachse investigated the shear‐wave echo power spectrum, and their experimental results showed that the shear‐wave spectrum changed with the stress.…”
Section: Introductionmentioning
confidence: 78%
“…The effect of overlapping modes and other interacting waves is to cause high-frequency modulation superimposed on the dispersion curve of the fundamental mode (Simpson, 1974;SanchezSalinero et al, 1987;Stoll et al, 1994b;Bautista, 1994). In order to reduce the effect of both organized and unorganized noise, a variety of different strategies have been employed.…”
Section: Introductionmentioning
confidence: 98%